2005
DOI: 10.1007/s00330-005-2866-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of focal renal perfusion defects in rabbits after sulphur hexafluoride-filled microbubble injection at low transmission power ultrasound insonation

Abstract: The aim of this study was to assess the feasibility of contrast-enhanced ultrasound (US) at low transmission power insonation for diagnosis of focal renal perfusion defects (RPDs) in rabbits. In seven adult New Zealand White rabbits focal RPDs were induced by polyvinyl alcohol embolizing particles (150-250 microm in diameter) injected into the abdominal aorta. Three other rabbits that were not subjected to embolization were considered as controls. Both kidneys were insonated at baseline and after injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Several studies have shown the potential of CEUS for improving the depiction of intrarenal blood flow, both in normal and pathological conditions. This technique has been found to be an effective way of depicting focal renal perfusion defects in pig and rabbit [7,[16][17][18], and preliminary investigation in man confirm these results [8,19,20]. To the best of our knowledge, however, no systematic investigation has been performed in man to test the accuracy of CEUS in comparison with established imaging techniques.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Several studies have shown the potential of CEUS for improving the depiction of intrarenal blood flow, both in normal and pathological conditions. This technique has been found to be an effective way of depicting focal renal perfusion defects in pig and rabbit [7,[16][17][18], and preliminary investigation in man confirm these results [8,19,20]. To the best of our knowledge, however, no systematic investigation has been performed in man to test the accuracy of CEUS in comparison with established imaging techniques.…”
Section: Introductionsupporting
confidence: 58%
“…Grey-scale ultrasonography (US) is highly insensitive for detecting acute renal infarction [7], and evaluation of renal perfusion with Doppler techniques has been limited by the relative insensitivity to low-velocity, low-amplitude flow states [8]. In particular, it can be very difficult, or even impossible, to differentiate ischemia from areas which appear poorly perfused with colour Doppler US [9,10], especially in elderly patients and in patients with underlying parenchymal disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…CEUS improves significantly the detection of non-perfused renal parenchymal zones appearing as single or multiple focal wedge-shaped areas of absent (Fig. 9), diminished, or delayed enhancement in comparison to the adjacent renal parenchyma [58,64]. Contrast-enhanced CT is still the reference imaging procedure for the diagnosis of acute pyelonephritis.…”
Section: Kidneysmentioning
confidence: 99%
“…10) or other vascular abnormalities, the re-filling curve revealed an increased time-to-peak and reduced slope of the wash-in tract and maximum amplitude [49, [67][68][69][70]. Animal models were initially employed to assess the capabilities of CEUS in the detection of renal perfusion defects [71][72][73][74][75], which appear as single or multiple focal wedge-shaped areas of absent, diminished or delayed contrast enhancement in comparison to the adjacent renal parenchyma (Figs. 11, 12) [76,77].…”
Section: Clinical Applications Of Organ Perfusionmentioning
confidence: 99%